Automated Indexing of SNOMED Statements into ICD - Wingert, F. (Methods of Information in Medicine, 1987)
A formal language is presented which is used to generate a transformation table for mapping SNOMED statements to ICD codes. Non-terminal symbols define parts of the SNOMED space, the highest order of which corresponds to ICD categories. Performance of the corresponding program system and remaining problems are described.
Keywords: Automated Indexing; ICD; SNOMED